The Development of Facilities and Infrastructure to Support Sustainable Coastal Tourism in Belitung Regency - Guni Refinda (Journal of Education on Social Science (JESS), 2017)
Tourism development was development that create added value in all aspects of tourism, ranging from infrastructure, attraction of tourism, and other aspects. One of the tourism developments, among others, the development of coastal tourism. The development must be carried sustainable coastal tourism development. Issues contained in the Pacific Islands Coastal Area Tourism was not accommodated well as the existence of its good infrastructure and the absence of supporting public facilities that can support the activities of visitors and tourism are less well-organized system of coastal tourism management by government Belitung regency. Based on this, the need for sustainable development of coastal areas. Facilities that support to achieved all the equipment in order to optimize the area of tourism.